Perceptions of Board Members on the Presence of Pharmacists as Strategic Leaders of Manufacturing Pharmaceutical Companies Operating in South Africa: A Qualitative Study - Nsovo Mayimele; Patrick Demana; Mothobi Keele (Business Ethics and Leadership, 2023)
Life-saving medicines are produced by manufacturing pharmaceutical companies (MPCs) with operations worldwide. The COVID-19 pandemic resulted in unequal access to vaccines, which led to advocacy around health rights and MPCs needing to prioritise saving lives over profits. This study aimed to determine the perceptions of board members of the largest listed MPCs in South Africa regarding the presence of pharmacists in the strategic leadership of MPCs, as custodians of medicines. A snowball sampling method was used to identify board members of the listed MPCs on the Johannesburg Stock Exchange (JSE). The board members were approached and requested to participate in their capacity. Data were collected through semi-structured interviews. Transcription, coding and narrative thematic analysis was applied under five (5) themes with emerging themes identified. A theoretical framework was developed to describe pharmacists at the strategic leadership of an MPC. The data collected were from five (5) respondents (80% male and 20% female), with a mean age of 57 years (SD±=2,24), from medical, business and pharmacy professional backgrounds. The respondents indicated a limited presence of pharmacists in the strategic leadership of MPCs, especially the larger ones. The reasons for the limited presence included the narrow diversity of corporate and leadership skills necessary to lead at a strategic level by pharmacists. Some of the barriers to entry into strategic leadership by pharmacists included the lack of recognition of pharmacy specialisations by the regulator of the pharmacy profession, a mismatch of skills of a graduate and what the industry needs and inadequate governance of the pharmacy profession in South Africa. The respondents agreed that having a pharmacist with ambition, business skills, and experience would benefit the MPC and users of products manufactured. The role and need for pharmacists in the strategic leadership of MPCs was established. It is clear, however, that while pharmacists have value in the leadership of MPCs, their entry should be supported by diversifying their skills in business, leadership and corporate management to extend their value beyond the technical level.
Keywords: 650; Leadership; Manufacturing